Tortious Liability of the Infected with Covid-19 for Transmission of the Infection. - suheb tmemy (الرافدین للحقوق, 2020)
The responsibility of the person carrying the Coronavirus infection is determined by the presence of a legal duty in the Public Health Law that requires social distancing and taking the important  health safety measures. the basis of the  responsibility for the infected person carrying the Coronavirus varies according to the following criteria. First, it is either for a fixed error, in which the burden of proof is placed on the injured  party by the defendant's change of the person's usual behavior. Secondly, it is based on the supposed error, as in the state’s responsibility for its negligence for the spread of the Corona pandemic. damage  in  responsibility  is represented by physical, material and moral one. The causality  in responsibility when the victim's injury  is caused by negligence of the infected person  who is transmitting the virus infection. This will be rejected by the foreign cause represented by the fault of the affected person himself,  and the force majeure and the action of others.